Android Application Design Based on Biomechanical Analysis for Pencak Silat Learning, it’s Effective ? - Dani Nur Riyadi; Aridhotul Haqiyah; Ari Bawono Putranto (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
Android provides an open platform for developers to create their own applications that can be used to help perform daily activities. Media can used to support online learning or training has an impact on learning the skill. This study aims to look into to develop android application based on biomechanical analysis of pencak silat. The video with biomechanical analysis of pencak silat in android application was created with the Kinovea application and RAD Studio 10.3 software developer. Kinovea is used to analyze biomechanics (angle of motion) and make slow-motion videos. The content developed is the basic techniques and single artistic jurus, the name of this android application is “Analisis Biomekanika Jurus Tunggal Pencak Silat (Tutorial)”. It has been found that 114 undergraduate students in physical education department who learn pencak silat material easily adapt to mobile learning. The application has not only been designed and tested, but it has also been in use for four months. This study's conclusions are based on practical rather than theoretical considerations.